Improved Solubility in Metavalently Bonded Solid Leads to Band Alignment, Ultralow Thermal Conductivity, and High Thermoelectric Performance in SnTe. (25th September 2022) - Liu, Yuqi; Zhang, Xuemei; Nan, Pengfei; Zou, Bo; Zhang, Qingtang; Hou, Yunxiang; Li, Shuang; Gong, Yaru; Liu, Qingfeng; Ge, Binghui; Cojocaru‐Mirédin, Oana; Yu, Yuan; et al.
Abstract: SnTe is an emerging Pb‐free thermoelectric compound that has drawn significant attention for clean energy conversion. Chemical doping is routinely used to tailor its charge carrier concentration and electronic band structures. However, the efficacy of dopants is often limited by their small solubility. For example, only 0.5% Ag can be incorporated into the SnTe matrix. Yet, significantly more Ag (>7%) can be dissolved if SnTe is alloyed with AgSbTe2 . This large enhancement of solubility can be understood from a chemical bonding perspective. Both SnTe and AgSbTe2 employ metavalent bonding as identified by an unusual bond‐rupture in atom probe tomography. Density functional theory calculations show that upon Ag doping the energy offset of the upmost two valence bands decreases significantly. This induces band alignment in SnTe, which results in an enhanced power factor over a broad temperature range. Moreover, the increased concentration of point defects and associated lattice strain lead to strong phonon scattering and softening, contributing to an extremely low κL of 0.30 Wm −1 K −1 . These synergistic effects contribute to a peak ZT of 1.8 at 873 K and a record‐high average ZT of ≈1.0 between 400 and 873 K in Sn0.87 Mn0.08 Sb0.08 Te–5%AgSbTe2 alloy. Abstract : A treasure map that separates different chemical bonding mechanisms is utilized to predict the miscibility of compounds. The solid solubility limit can be greatly improved by alloying compounds utilizing metavalent bonding. The increased solubility of Ag in SnTe by alloying with AgSbTe2 leads to a strong band alignment, ultralow lattice thermal conductivity, and exceptional maximum and average ZT values.